Rehabilitation and Repression: Reassessing their Ideological Embeddedness - Mascini, Peter (The British journal of criminology, 2006)
For over a century, scholars and practitioners have assumed rehabilitation stands as the progressive opposite of repression. Elaborating on previous warnings and anomalous findings, a representative survey of the Dutch population (N = 1,892) points out that this received view is flawed. When measured separately, no significant correlation exists between support for rehabilitation and support for repression, rehabilitation is equally popular among the constituencies of conservative and progressive political parties, and no negative relationship exists between rehabilitation and authoritarianism. Decriminalization rather than rehabilitation proves to constitute the progressive converse of repression. By way of conclusion, we discuss the remarkable persistence of the received view reassessed in this paper, even in the face of convincing earlier contradictory evidence